Implementasi Kesadaran Lingkungan dan Pengembangan Pendidikan Islam di Desa Purut Kabupaten Probolinggo - Mukhamad Ainul Yaqin; Very Ardana; Muhammad Hegel Arta Pramudya (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The implementation of environmental awareness through faith-based education at Madrasah Diniyah Baitussalam in Purut -Lumbang, Probolinggo. The community service program used an educational and participatory approach, integrating religious values with environmental education. Activities included environmental lessons, collective clean-up actions, and the provision of facilities such as trash bins and school signage. Results indicate increased environmental awareness among students and community members, along with strengthened collaboration between the madrasah and local residents. The integration of environmental education with religious teachings proved effective in fostering environmentally conscious behavior both spiritually and socially. Madrasah diniyah plays a strategic role as an agent of change in rural areas, and this program serves as a model for localized environmental education in similar communities.